2023
DOI: 10.1101/2023.04.25.538229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase-specific stimulation reveals consistent sinusoidal modulation of human corticospinal excitability along the oscillatory beta cycle

Abstract: The responsiveness of neuronal populations to incoming information fluctuates. Retrospective analyses of randomly applied stimuli reveal a neural input-output relationship along the intrinsic oscillatory cycle. Prospectively harnessing this biological mechanism would necessitate frequency- and phase-specificity, intra- and inter-individual consistency, and instantaneous access to the oscillatory cycle. We used a novel real-time approach to electroencephalography-triggered transcranial magnetic stimulation to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…A recent advancement in EEG-triggered TMS (21) leverages a non-predictive, real-time integrated measurement and stimulation approach to achieve precise, phase-specific targeting with minimal standard deviations (0.4°at 4 Hz to 4.3°at 40 Hz). Utilizing this technique to target eight phases across ten frequencies (4-40 Hz) revealed consistent, phase-dependent effects, particularly a sinusoidal CSE modulation at 24 Hz, with optimal CSE at the transition from the trough to the rising flank, observed both within and across sessions and individuals (22). Notably, a post-hoc analysis in another study confirmed this sinusoidal modulation exclusively between 23 and 25 Hz (23).…”
Section: Introductionmentioning
confidence: 77%
“…A recent advancement in EEG-triggered TMS (21) leverages a non-predictive, real-time integrated measurement and stimulation approach to achieve precise, phase-specific targeting with minimal standard deviations (0.4°at 4 Hz to 4.3°at 40 Hz). Utilizing this technique to target eight phases across ten frequencies (4-40 Hz) revealed consistent, phase-dependent effects, particularly a sinusoidal CSE modulation at 24 Hz, with optimal CSE at the transition from the trough to the rising flank, observed both within and across sessions and individuals (22). Notably, a post-hoc analysis in another study confirmed this sinusoidal modulation exclusively between 23 and 25 Hz (23).…”
Section: Introductionmentioning
confidence: 77%